Unveiling Firm Value Dynamics Amidst COVID-19: Mengungkap Dinamika Nilai Perusahaan di Tengah COVID-19 - Endah Permatasari; Eny Maryanti (Academia Open, 2024)
This research investigates the impact of company size, leverage, company growth, and profitability on firm value in the food and beverage sector amidst the COVID-19 pandemic. Utilizing Partial Least Square regression and data from Indonesia Stock Exchange-listed companies, the study finds that company size, leverage, and profitability significantly influence firm value, while company growth does not. Moreover, company size affects profitability, while leverage and company growth do not notably impact profitability. Profitability serves as an intermediary between company size and firm value but does not mediate the relationship between leverage, company growth, and firm value. These findings highlight the importance of considering multiple factors concurrently in assessing firm value, particularly in times of crisis, offering valuable insights for managerial decision-making and policy formulation to enhance business resilience and sustainability. Highlights: 1. Analyzing firm value during COVID-19, emphasizing company size and profitability.2. Company size, leverage, and profitability significantly influence firm value.3. Profitability acts as a mediator, impacting firm value dynamics. Keywords: Firm value, COVID-19, Company factors, Profitability, Partial Least Square regression